Knowledge, attitudes and behaviors of the Italian population towards Neisseria meningitidis, Streptococcus pneumoniae and HPV diseases and vaccinations: A cross-sectional multicentre study. (December 2016) - de Waure, C.; Quaranta, G.; Ianuale, C.; Panatto, D.; Amicizia, D.; Apprato, L.; Campanella, P.; Colotto, M.; De Meo, C.; Di Nardo, F.; Frisicale, E.M.; La Milia, D.I.; et al.
Abstract: Objectives: This study addressed knowledge of Streptococcus pneumoniae, Neisseria meningitidis and human papillomavirus (HPV), and attitudes and behaviours towards vaccines against them. Study design: This is a cross-sectional, multicentre study. Methods: Data were collected through a questionnaire administered to 530 adults who accessed four Departments of Prevention of the Italian National Health Service in 2013. Results: Less than 50% of people gave the right answer to all the questions concerning the three diseases, but 96.2%, 94% and 92.7% agreed with the importance of vaccination against N. meningitidis, S. pneumoniae and HPV, respectively, and 58.4% expressed own willingness to have their children vaccinated with N. meningitidis B vaccine. The attitude towards vaccination was more positive in women for N. meningitidis and in people having children for HPV. Furthermore, individuals giving correct answers to all knowledge items were more in favour of both HPV and S. pneumoniae vaccination. A total of 68.8%, 82.6% and 84.5% of respondents vaccinated their own children against N. meningitidis C, S. pneumoniae and HPV, respectively. About 50% of the respondents reported paediatricians' or other health professionals' recommendations as the main reason for vaccination. Conclusions: Vaccinations may be promoted through actions aimed at increasing citizens' knowledge. Health professionals should be educated to actively provide information on vaccinations in a clear, comprehensive and effective way. Highlights: In Italy, the GP is the least consulted source of information about HPV. However, the GP is the main source of information about Neisseria meningitidis and Streptococcus pneumoniae . Knowledge can be largely improved (and, regarding HPV, is much poorer among males). Paediatrician's recommendations play a major role in motivating vaccinations. Attitudes towards the vaccine against N. meningitidis B are too poor.